1990
DOI: 10.2134/agronj1990.00021962008200050015x
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Management of a Crimson Clover Cover Crop For No‐Tillage Corn Production

Abstract: Legume cover crops are valuable N sources for no‐tillage corn (Zea mays L.). However, little research has been done in assessing the management options for legume cover crops. Field studies were conducted on a Coastal Plain Matapeake silt loam soil (fine‐silt, mixed, mesic Typic Hapludult) from 1983 through 1986 to determine the effects of various harvest management schedules on total N contribution of legume cover crops, subsequent corn grain and silage yields, and total forage (combined cover crop and corn h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Compared to the removal of berseem herbage, its return to the soil/crop produced an increase in the yields of wheat straw and grain in the subsequent growing season, particularly when the herbage was chopped. Holderbaum et al (1990) found that in corn ( Zea mays L.) following a crimson clover cover crop both grain and silage yields were higher when clippings were returned rather than removed. Chopping the herbage resulted in a small but significant increase in wheat yield compared to returning it unchopped; according to several authors (Guérif, 1979; Swift et al, 1979; Chesson, 1997; Fruit et al, 1998), reducing the size of the mulching material may increase the decomposition of biochemical components and enhance the exchange of nutrients with the surrounding soil.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the removal of berseem herbage, its return to the soil/crop produced an increase in the yields of wheat straw and grain in the subsequent growing season, particularly when the herbage was chopped. Holderbaum et al (1990) found that in corn ( Zea mays L.) following a crimson clover cover crop both grain and silage yields were higher when clippings were returned rather than removed. Chopping the herbage resulted in a small but significant increase in wheat yield compared to returning it unchopped; according to several authors (Guérif, 1979; Swift et al, 1979; Chesson, 1997; Fruit et al, 1998), reducing the size of the mulching material may increase the decomposition of biochemical components and enhance the exchange of nutrients with the surrounding soil.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of nonleguminous cover crops or mixture of leguminous and nonleguminous cover crops to reduce NO 3 –N leaching is well recognized (Brandi‐Dohrn et al, 1997; Owens, 1990). The effectiveness of various types of cover crops or combination of different cover crop species on soil N availability and the productivity of succeeding crops has been extensively evaluated (Holderbaum et al, 1990; Clark et al, 1997a; Kuo et al, 1996, Smith et al, 1987). It is quite clear from the literature that N content or C/N ratio of cover crop is a principal determinant of cover crop residue effects on soil N availability after residue incorporation into soil (Hargrove, 1986; Ranells and Wagger, 1996; Smith et al, 1987).…”
mentioning
confidence: 99%
“…Removing top growth of legume or rye cover crops may leave little, if any, effects on yield of succeeding corn or sorghum [ Sorghum bicolor (L.) Moench] (Doll and Link, 1957; Raimbault et al, 1990). Even with a slight reduction in corn yield when the top growth of crimson clover ( Trifolium incarnatum L.) was removed, the reduction was more than compensated for by the harvested crimson clover (Holderbaum et al, 1990). The total biomass yield under this residue management system was still higher than the total corn silage yield with the incorporation of the clover residue into the soil.…”
mentioning
confidence: 99%
“…was evident during the cool, wet, late winter period in 1989 and may have reduced crimson clover DM production by corn planting time. Sclerotinia rot has been reported in reseeded crimson clover stands during cool, moist, late winter and early spring periods, especially when considerable fall growth occurred (Holderbaum et al, 1990a;Myers and Wagger, 1991).…”
Section: Crimson Clover Dry Matter Production and Nitrogen Contentmentioning
confidence: 99%
“…Recent studies with crimson clover as a cover crop in no-tillage systems showed corn yield responded to as much as 90 kg ha-l of fertilizer N in seasons with adequate rainfall distribution (Ebelhar et al, 1984;Fleming et al, 1981;Holderbaum et al, 1990a). However, corn grain yield following crimson clover, rye (Secale cereale L.), or hairy vetch (Vicia villosa Roth.)…”
mentioning
confidence: 99%